Prevention of preterm delivery with vaginal progesterone in women with preterm labour (4P): randomised double‐blind placebo‐controlled trial. (11th September 2014) - Martinez de Tejada, B; Karolinski, A; Ocampo, MC; Laterra, C; Hösli, I; Fernández, D; Surbek, D; Huespe, M; Drack, G; Bunader, A; Rouillier, S; López de Degani, G; et al.
<x xml:space="preserve">Abstract</x> Objective To evaluate the effectiveness of 200 mg of daily vaginal natural progesterone to prevent preterm birth in women with preterm labour. Design Multicentre, randomised, double‐blind, placebo‐controlled trial. Setting Twenty‐nine centres in Switzerland and Argentina. Population A total of 385 women with preterm labour (240/7 to 336/7 weeks of gestation) treated with acute tocolysis. Methods Participants were randomly allocated to either 200 mg daily of self‐administered vaginal progesterone or placebo within 48 hours of starting acute tocolysis. Main outcome measures Primary outcome was delivery before 37 weeks of gestation. Secondary outcomes were delivery before 32 and 34 weeks, adverse effects, duration of tocolysis, re‐admissions for preterm labour, length of hospital stay, and neonatal morbidity and mortality. The study was ended prematurely based on results of the intermediate analysis. Results Preterm birth occurred in 42.5% of women in the progesterone group versus 35.5% in the placebo group (relative risk [RR] 1.2; 95% confidence interval [95% CI] 0.93–1.5). Delivery at <32 and <34 weeks did not differ between the two groups (12.9 versus 9.7%; [RR 1.3; 95% CI 0.7–2.5] and 19.7 versus 12.9% [RR 1.5; 95% CI 0.9–2.4], respectively). The duration of tocolysis, hospitalisation, and recurrence of preterm labour were comparable between groups. Neonatal morbidity occurred in 44 (22.8%) cases on progesterone versus 35 (18.8%) cases on placebo (RR: 1.2; 95% CI 0.82–1.8), whereas there were 4 (2%) neonatal deaths in each study group. Conclusion There is no evidence that the daily administration of 200 mg vaginal progesterone decreases preterm birth or improves neonatal outcome in women with preterm labour.